Pengaruh Media Podcast Terhadap Keterampilan Menyimak Teks Hikayat Peserta Didik Kelas X SMA Negeri 2 Makassar - Muh. Danis; Usman; Nur Masyrah Syam (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the effect of using podcasts on the listening skills of Class X SMA Negeri 2 Makassar students. This research is a type of Quantitative research with the research design used is One Group Pretest-Posttest Design. The research sample totalled 36 students in Class X.2 SMA Negeri 2 Makassar. The instrument used in the study was a multiple choice test. Data analysis used descriptive statistics and inferential statistics. The results showed that the listening skills of hikayat text before using podcasts were categorised as quite skilled with an average score of 56.22. Listening skills after using podcasts are categorised as skilled with an average score of 77.22. The results of hypothesis testing showed that the sig. (2-tailed) value was 0.000 <0.05. Thus, there is an effect of using podcasts on the listening skills of Class X SMA Negeri 2 Makassar students.